Management strategy of halal tourism (case study in Central Lombok local government) / I Kadek Dwi Kencana Putra ...[et al.] - Kencana Putra, I Kadek Dwi; Atikah, Siti; Rakhmawati, Intan (2019)
In 2015, Lombok have won The World's Best Halal Honeymoon Destination and The World's Best Halal Tourism Destination in World Halal Tourism Awards (WHTA). But for Central Lombok Regency Government, although have that predicate, but the influence to income tax local government (al-wazha-if) from hotel and entertainment precisely decrease. Because of that, since that year, the West Nusa Tenggara Provincial Government through its regency government seeks to make Lombok as eco-halal tourism too.